Thermal condensations in hydrostatic coronal loops - Mendoza Briceño, César (Ciencia, 1970)
The equations of thermal equilibrium along a symmetric coronal loop with a constant cross-sectional area including gravity is investigated. A coronal heating function depending on distance along the loop is considered. The effects of varying the values of the parameters involved in the governing equations are also analyzed. It is found that there is a critical decay length of the heating, below which a hot coronal loop does not exist. It is suggested that thermal non-equilibrium occurs, allowing for the existence of catastrophic cooling. In addition, it is shown that prominence-type equilibria are possible. A distortion of the magnetic field simulating a dip is also studied.